The Role of Organization Capital in Improving Company Performance through Inventory Efficiency: Analysis Literature and its Implications - Ngadi Permana; Fardan, Mohamad Rakel (Journal of Economic and Leadership, 2024)
This qualitative literature review explores the role of organizational capital in enhancing firm performance through inventory efficiency. The study finds that organizational capital positively impacts inventory efficiency by fostering innovation, improving stakeholder orientation, and reducing financial constraints. It also strengthens the relationship between inventory efficiency and firm performance, suggesting that investment in organizational capital can lead to significant competitive advantages. However, the review highlights limitations, including a focus on US-based firms and a lack of exploration into specific elements of organizational capital, such as organizational culture and leadership styles. These findings underscore the need for further empirical research across diverse international contexts to deepen the understanding of organizational capital's impact on inventory management